Peran Moderasi Kepemimpinan dalam Pengujian Akuntabilitas Kinerja Pemerintah - Kamalia, Alfia; Firmansyah, Amrie (Penerbit Goodwood, 2024)
Purpose: This study examines the effects of the government's internal control system and the implementation of good public governance on government performance accountability. In addition, leadership style can affect the government's internal control system and implementation of good public governance. Methodology: The testing method used in this study was a quantitative method. This study used a questionnaire to collect data. The questionnaire was distributed by random sampling through Google Forms media to all civil state apparatuses at the Ministry of Communication and Information. Fifty questionnaires were obtained for distribution was 50 respondents. Hypothesis testing was performed using a Structural Equation Model (SEM). Results: The government's internal control system and implementation of good public governance positively affect government performance accountability. The leadership style weakens the government's internal control system on government performance accountability. Leadership style does not affect the application of good public governance to government performance accountability. Limitations: The questionnaire items were compiled based on limited sources, causing some items to be declared invalid. The distribution of questionnaires via Google Forms was not believed to be valid for the answers given by respondents and could not be confirmed directly. Contribution: This research is expected to improve the government's accountability for its performance and serve as a reference for further research.